Aboriginal and Torres Strait Islander health research and the conduct of longitudinal studies: issues for debate - Natalie Grove; Mark Brough; Condy Canuto; Annette Dobson (Elsevier, 2003)
Abstract The National Health and Medical Research Council, Research Agenda Working Group (RAWG), and the literature on Indigenous health have identified the need to fill gaps in descriptive data on Aboriginal and Torres Strait Islander health and noted both the lack of research with urban populations and the need for longitudinal studies. This paper presents some of the broad ethical and methodological challenges associated with longitudinal research in Indigenous health and focuses particularly on national studies and studies in urban areas. Our goal is to advance debate in the public health arena about the application of ethical guidelines and the conduct of longitudinal studies in Aboriginal and Torres Strait Islander communities. We encourage others to offer their experiences in this field.